EFEKTIVITAS KELAS IBU SEBAGAI UPAYA PENINGKATAN PENGETAHUAN IBU HAMIL TERHADAP PEMERIKSAAN KEHAMILAN DI DESA PUKDALE KECAMATAN KUPANG TIMUR KABUPATEN KUPANG TAHUN 2023 - Gusman, Avelina Paskalia; Duka, Maria Magdalena Theofila; Manek, Brigita Dina; Ilma, Nabilah Nurul; Mangngi, Atalia Pili (Jurnal Abdi Insani, 2024)
Mother's knowledge and skills are very important during pregnancy, childbirth, postpartum, infant and toddler care. The Pregnant Mother Class is a study group for expectant mothers about overall health for pregnant women. Classes for pregnant women are facilitated by midwives using the mother class package, namely the KIA book, guidelines for implementing classes for pregnant women, guidelines for administering classes for mothers under five, pregnant women and lactating mothers, handouts for class facilitators for mothers under five. This community service activity aims to provide education for pregnant women and help increase the knowledge and skills of pregnant women during pregnancy, childbirth, postpartum care, baby care, myths about sexually transmitted diseases through pregnant women's class activities. The methods used in this activity are lectures, brainstorming and discussions. This activity will be held on Monday, December 18 2023 starting at 09.00 WITA and ending at 11.00. The target is all pregnant women in Pukdale Village from the first trimester to the third trimester of pregnancy. The results of this activity showed that 15 pregnant women (88%) had increased their knowledge about the importance of pregnancy checks. The resource person for this activity is a lecturer from STIKes Maranatha Kupang. This community service activity has been carried out to increase pregnant women's knowledge about the importance of routine pregnancy checks so that pregnancy problems can be detected early.